Four new complete mitochondrial genomes of Gobioninae fishes (Teleostei: Cyprinidae) and their phylogenetic implications - Tang, Yongtao; Ma, Wenwen; Chen, Xin; Nie, Guoxing; Zhou, Chuanjiang (PeerJ, 2024)
The subfamily Gobioninae is one of the most diverse fish groups within Cyprinidae. Their taxonomy and phylogenetic relationships are not completely resolved. In this study, the complete mitochondrial genomes (mitogenome) of four Gobioninae species (Microphysogobio elongatus, Microphysogobio chinssuensis, Gobio rivuloides and Rhinogobio nasutus) were sequenced and compared. The mitogenomes of four species ranges from 16603 bp to 16609 bp in length, consisting of 13 protein-coding genes (PCGs), 22 tRNA genes, two rRNA genes, and a control region. Most PCGs had significant codon usage bias. Except for the tRNASer (GCT), all the nucleotide substitutions of tRNA loops higher than the stems could fold into a stable secondary structure. The nucleotide compositions of Gobioninae mitogenome were biased toward A/T, and NAD4 was subjected to low purification selection and had a faster evolution rate among 13 PCGs. Bayesian inference and maximum likelihood phylogenetic analyses showed the consistent results. The four sequenced species clustered together with their congener species. However, more samples and mitogenome data are needed to untangle the phylogenetic relationships among genera Microphysogobio, Romanogobio, Hugobio, Biwia and Platysmacheilus.
Keywords: Gobioninae; Mitochondrial genome; Phylogenetic relationships